Efficient network traffic management and intelligent decision-making through machine learning and DNS log analysis - Hossain, Syed Abed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2023.